The Effect of Instagram in Blended Learning on Students’ Parts of Speech Achievement at the Tenth Grade of SMAN 2 Kendari - Syamsuddin, Dwi Rezky; Suhartini, Lelly; Rohmana, Rohmana (Journal of Teaching of English, 2021)
The objective of this study was to investigate the significant effect of Instagram in blended learning on students’ parts of speech achievement at the tenth grade of SMAN 2 Kendari. This study used pre-experimental design. The sample was the tenth graders of SMAN 2 Kendari in academic year 2019/2020 which consisted of 33 students. To collect the data, the researcher used grammar test about parts of speech. The data were analyzed using application of SPSS 16 version software. The result of this study showed that using Instagram in blended learning had significant effect on parts of speech achievement of the students at the tenth grade of SMAN 2 Kendari. It was indicated by the result of the statistical analysis where it was found that tcount (9.345) was higher than ttable (0.05) and probability value (0.00) was lower than ttable (0.05). As the result, it can be concluded that using Instagram in blended learning is effective on students’ parts of speech achievement at the tenth grade of SMA Negeri 2 Kendari.